Excessive Gingival Display: An Updated Review for Dentists, Clinical Pathologists, and Nursing - Alqahtani, Farraj Hamad Faleh; Al-Otaibi , Lamyaa Mubarak Abdullah; Nasser Al, Nasser Jamaan; Al Baqshi, Anesah; Alzayer, Zahra Ali Mohammed; Alotaibi, Elian Sayel; Alsharari, Muhannad Sabih Basheer; Alonazey, Sultan Lbrahim; Alsharar, Eid Shaman Mohammed; Bashakur, Noof Agail; Al Ruwaili, Faisal Saud Sharidah; Al Otaibie, Samia Sultan; et al. (Journal of Ecohumanism, 2024)
Excessive gingival display, commonly known as a "gummy smile," is an aesthetic concern characterized by the overexposure of maxillary gingiva during smiling. It can result from various factors, including vertical maxillary excess (VME), hypermobile upper lip, altered passive eruption, gingival hyperplasia, and dentoalveolar extrusion. The condition affects approximately 10% of individuals aged 20–30, with a higher prevalence in women. It can significantly impact self-esteem and psychological well-being, making accurate diagnosis and effective management essential.This review aims to provide an updated overview of the etiology, diagnosis, and treatment options for excessive gingival display, emphasizing the importance of a multidisciplinary approach to achieve optimal aesthetic and functional outcomes.A comprehensive evaluation, including medical history, facial and lip analysis, periodontal examination, and radiographic imaging, is essential for diagnosing the underlying cause of a gummy smile. Treatment modalities range from minimally invasive procedures, such as botulinum toxin and hyaluronic acid injections, to surgical interventions like gingivectomy, lip repositioning, and orthognathic surgery. Orthodontic treatment may also be employed in select cases.The prognosis for patients with a gummy smile is generally favorable, with most cases showing significant improvement following appropriate treatment. Less invasive options provide temporary results, while surgical interventions offer more permanent solutions. Accurate diagnosis and tailored treatment plans are critical for achieving satisfactory outcomes.Excessive gingival display is a multifactorial condition requiring a personalized treatment approach. Collaboration among dental professionals, including periodontists, orthodontists, and oral surgeons, is essential for effective management. Addressing both the clinical and psychological aspects of the condition enhances patient satisfaction and quality of life.